A Regulatory Feedback Loop between HIF-1α and PIM2 in HepG2 Cells - Yu, Zhenhai; Zhao, Xiaoping; Ge, Yingying; Zhang, Teng; Huang, Liangqian; Zhou, Xiang; Xie, Lei; Liu, Jianjun; Huang, Gang (PLOS ONE, 2014)
To survive under hypoxic conditions, cancer cells remodel glucose metabolism to support tumor progression. HIF transcription factor is essential for cellular response to hypoxia. The underlying mechanism how HIF is constitutively activated in cancer cells remains elusive. In the present study, we characterized a regulatory feedback loop between HIF-1α and PIM2 in HepG2 cells. Serine/threonine kinase proto-oncogene PIM2 level was induced upon hypoxia in a HIF-1α-mediated manner in cancer cells. HIF-1α induced PIM2 expression via binding to the hypoxia-responsive elements (HREs) of the PIM2 promoter. In turn, PIM2 interacted with HIF-1α, especially a transactivation domain of HIF-1α. PIM2 as a co-factor but not an upstream kinase of HIF-1α, enhanced HIF-1α effect in response to hypoxia. The positive feedback loop between PIM2 and HIF-1α was correlated with glucose metabolism as well as cell survival in HepG2 cells. Such a regulatory mode may be important for the adaptive responses of cancer cells in antagonizing hypoxia during cancer progression.